Flow around a slotted circular cylinder at various angles of attack - Gao, Dong-Lai; Chen, Wen-Li; Li, Hui; Hu, Hui (Experiments in fluids, 2017)
We experimentally investigated the flow characteristics around a circular cylinder with a slot at different angles of attack. The experimental campaign was performed in a wind tunnel at the Reynolds number of Re = 2.67 × 10 4 . The cylindrical test model was manufactured with a slot at the slot width S = 0.075 D ( D is the diameter of the cylinder). The angle of attack α was varied from 0° to 90°. In addition to measuring the pressure distributions around the cylinder surface, a digital particle image velocimetry (PIV) system was employed to quantify the wake flow characteristics behind the baseline cylinder (i.e., baseline case of the cylinder without slot) and slotted cylinder at various angles of attack. Measurement results suggested that at low angles of attack, the passive jet flow generated by the slot would work as an effective control scheme to modify the wake flow characteristics and contribute to reducing the drag and suppressing the fluctuating lift. The flip-flop phenomenon was also identified and discussed with the slot at 0° angle of attack. As the angle of attack α became 45°, the effects of the slot were found to be minimal. When the angle of attack α of the slot approached 90°, the self-organized boundary layer suction and blowing were realized. As a result, the flow separations on both sides of the test model were found to be notably delayed, the wake width behind the slotted cylinder was decreased and the vortex formation length was greatly shrunk, in comparison with the baseline case. Instantaneous pressure measurement results revealed that the pressure difference between the two slot ends and the periodically fluctuating pressure distributions would cause the alternative boundary layer suction and blowing at α = 90°.